Yoga Based on Shalat Movement to Develop Post-Pandemic Children’s Self Control : English - Hayati, Miratul; Salasati, Putri (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – This study aimed to develop yoga activities based on prayer movements to train children’s self-control. The subjects in this study were early childhood children in the TK B group. Design/methods/approach – This research uses development research (R&D). Feasibility assessment of the development of prayer movement-based Yoga to train children’s self-control based on the assessment of media experts, yoga experts, and group B students as test subjects. Analysis using qualitative and quantitative data analysis, collecting data using interview guidelines, observation documentation, and questionnaires. Findings – The results showed that the development of prayer movement-based Yoga through a series of trials and expert validation, was workable for training children’s self-control which included (1) the ability to regulate behavior, (2) the ability to regulate stimuli, (3) the ability to consider things and events, ( 4) the ability to evaluate events and things positively, and (5) the ability to determine actions. Research implications/limitations – This research can be the basis and guideline for further research related to Yoga based on prayer movements in training self-control in early childhood. Researchers suggest that there are other studies regarding using Yoga based on prayer movements to train children’s self-control and other abilities from an early age. The drawback of this study is that it did not conduct a practical test due to time constraints. Practical implications – This research produces Yoga products based on prayer movements. Teachers and parents can use it to train children’s self-control from childhood. So that the results of developing this product can be helpful, and other schools can practice it in training children’s self-control or other abilities after the pandemic that hit the world. Originality/value – The development of Yoga based on prayer movements can train the self-control abilities of early childhood. Researchers recommend using prayer movement-based yoga in kindergartens to train children’s self-control. Paper type Research paper